Agrarian Reform in Occidental Negros, Philippines - Tan, Sabrina Joy; Sinaga, Randa Putra Kasea (Jurnal Kajian Agraria dan Kedaulatan Pangan (JKAKP), 2024)
Despite government implementation of agrarian reform programs, poverty and violence remain prevalent issues faced by communities dealing with agrarian problems. The dynamics of agrarian issues in Negros Occidental, a region rich in violent events related to agrarian reform policies, highlight the challenges. While the Philippine government initiated agrarian reform programs in the 1970s to redistribute land to landless farmers, aiming to promote wealth distribution and improve socio-economic conditions, implementation has not been successful. Bureaucratic inefficiencies and opposition hinder the reform process, leaving many vulnerable peasants economically insecure and in poverty. The complexity of agrarian dynamics in Negros Occidental involves strong opposition from landlords to agrarian reform, leading to systematic and structural violence. The engagement of various actors, such as the government, peasant communities, and corporations, in agrarian conflicts underscores the need for inclusive and sustainable approaches to agrarian reform in the Philippines for empowering marginalized communities and achieving social justice for peasants and rural peoples.